2016
DOI: 10.1590/s1679-87592016111706402
|View full text |Cite
|
Sign up to set email alerts
|

The structural heterogeneity of an urbanised mangrove forest area in southeastern Brazil: Influence of environmental factors and anthropogenic stressors

Abstract: The objective of this study is to evaluate the characteristics of the forest in an urbanised mangrove using vegetation structure and abiotic conditions to distinguish habitat heterogeneity/quality. A total of 16 points in Vitória Bay were selected in the fringe and basin forests. The variables evaluated were height and diameter of the individual trees, basal area, density, dominance, interstitial water, litter mass, grain size, organic matter and anthropogenic influences. The results indicated that the mangrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
1
15
0
4
Order By: Relevance
“…Despite this, the occurrence of the associate species in this mangrove which are basically found in fresh water zones may entail their adaptation to brackish habitats. The dominance of Rhizophora mangle in this mangrove aligns with the findings of Strauch et al 18 and Zamprogno et al 19 while working in mangroves of Bahamas Island and mangrove forest in southeastern Brazil. Elsewhere, Savory 20 and Abere & Ekeke 21 had reported Rhizophora racemosa to be the pioneer mangrove species on the shorelines of Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…Despite this, the occurrence of the associate species in this mangrove which are basically found in fresh water zones may entail their adaptation to brackish habitats. The dominance of Rhizophora mangle in this mangrove aligns with the findings of Strauch et al 18 and Zamprogno et al 19 while working in mangroves of Bahamas Island and mangrove forest in southeastern Brazil. Elsewhere, Savory 20 and Abere & Ekeke 21 had reported Rhizophora racemosa to be the pioneer mangrove species on the shorelines of Nigeria.…”
Section: Discussionsupporting
confidence: 89%
“…Mangrove loss around cities has primarily been reported for Africa, Latin America and India (Benfield, Guzman, & Mair, ; Mohamed, Neukermans, Kairo, Dahdouh‐Guebas, & Koedam, ; Nagendra, Sudhira, Katti, & Schewenius, ; Nfotabong‐Atheull, Din, & Dahdouh‐Guebas, ; Nortey, Aheto, Blay, Jonah, & Asare, ; Obiefuna, Nwilo, Atagbaza, & Okolie, ; Olagoke, Mwihaki, Bosire, & Berger, ; Vaz, ; Zamprogno et al, ). This agrees with predictions of ecological vulnerability in low‐ and lower‐middle‐income regions owing to rapid urbanization and management lags (Baird, ; McGranahan, Balk, & Anderson, ; Seto et al, ; United Nations Environment Program, ).…”
Section: Introductionmentioning
confidence: 99%
“…But evidence of urban mangrove reforestation after the implementation of tighter restrictions in low‐, middle‐ and high‐income regions proposes regulatory strength as an effective agent of urban mangrove conservation (Burt, ; DasGupta & Shaw, ; Martinuzzi, Gould, Lugo, & Medina, ; Pham & Yoshino, ). Furthermore, a number of studies have reported spatial heterogeneities in mangrove changes around cities (Mohamed et al, ; Nagendra et al, ; Nfotabong‐Atheull et al, ; Vaz, ; Zamprogno et al, ), with the majority suggesting that much of the loss associated with urban mangroves is occurring at settlement edges, not in city centres.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, mangrove coverage in the largest cities is decreasing faster than overall rates from corresponding countries [14]. In some cases, this loss results in fragmented forests consisting of novel species assemblages and size classes [15][16][17][18]. There are cases of expanding urban mangrove coverage [19,20], although the young forests may contain less biomass [21].…”
Section: Introductionmentioning
confidence: 99%